Kinerja Keuangan dan Risiko BUMDes (Studi Kasus Pada BUMDes Suka Pura) - Ni Luh De Erik Trisnawati (ARTHA SATYA DHARMA, 2021)
The purpose of this study was to find empirical evidence regarding the relationship between risk and financial performance at BUMDes Suka Pura. Effective risk management will keep liquidity safe and minimize losses so that financial performance improves. The risks tested are liquidity risk and credit risk, which are measured through ratio analysis to the 2018 to 2020 financial statements. The Data Analysis technique used is Multiple Regression with the help of SPSS. The results of this study found that liquidity risk has a significant positive effect on financial performance. Credit risk has a significant negative effect on financial performance. The risks closest to BUMDes that manage savings and loan units are liquidity risk and credit risk. Keeping liquidity safe through effective lending will reduce the possibility of credit risk.